Professional relationships in palliative care decision making - Lee, S.; Kristjanson, Linda; Williams, Anne (Springer, 2008)
Background: Decision making in the context of palliative care is particularly complex given the unpredictable illness trajectories experienced by patients and the number of individuals who may be part of decision-making processes. This study aimed to describe the significant issues that influence the processes of care decision making, from the perspective of patients with advanced illness. Methods: Patients (14), family members (7) and health professionals (18) were interviewed and field observations (100 h) of decision-making practices were undertaken in two Australian palliative care services. A systematic approach using grounded theory to collect and analyse the data was used to develop a theory of decision making from the patient's perspective. Results: The main issue experienced by palliative care patients was identified as a lack of involvement in decision making. One of the significant factors affecting the decision process is the type of relationship with health professionals that patients believe enhances their involvement in decision making. This was determined by the manner and focus of the health professional, their trustworthiness as well as the healthcare culture and environment. This paper provides a greater understanding of the perspective of patients in relation to their involvement in decisions related to palliative care.